Ze starego do nowego świata. Obraz miasta w Listach z podróży do Ameryki Henryka Sienkiewicza - Pietrzak, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article aims to present the linguistic means (stylistic methods and vocabulary) used by Henryk Sienkiewicz to create the image of European and American cities in his Listy z podróży do Ameryki. The author of the article also analyses the descriptions of experiencing large and modern cities, proving that the images of European and Americancities perceived and described from a European’s perspective were contrasted. It is the consequence of perceiving European agglomerations as cultural and historic centres cultivating traditional values in contrast to the mainly industrial American cities serving as trading centres full of action and fast-paced life. The choice of linguistic means used to describe urban buildings was determined by the viewpoint of the perceiving subject and the perspective from which the act of perceiving was accomplished.